Potential of Neglected and Underutilized Yams (Dioscorea spp.) for Improving Nutritional Security and Health Benefits - Padhan, Bandana; Panda, Debabrata (Frontiers in Pharmacology, 2020)
Food and nutritional security are the major concerns in many countries of the world and may have potential to contribute to sustainable food systems under climate change. To address the food and nutritional insecurity, it has become extremely important to diversify the present-day agricultural system as well as to search for alternative food and feed ingredients. Some wild root and tuber crops occupy a remarkable position towards food security of the developing world due to their high calorific value and superior carbohydrate content. Yam (Dioscorea spp.) provides food and medicines to millions of people in the world especially in the tropics and sub tropics. It is recognised as the fourth most important tuber crop after potatoes, cassava and sweet potatoes. It contributes about 10% of the total root and tubers production around the world. Yams also considered as famine food and plays a prime role in the food habit of small and marginal rural families and forest-dwelling communities during the food scarcity periods. These species are unique for their food, medicinal and economic values but their wider utilization is limited due to the presence of anti-nutritional compositions. This paper describes the ethnobotany of yam species in relation to their nutritional, anti-nutritional and pharmacological properties and highlights the potentiality for food and nutritional security for combating the ‘hidden hunger’ caused by micronutrient deficiencies.